Perubahan Tren Pariwisata: Hunian Hotel dan Pendapatan Asli Daerah Kabupaten Tapanuli Tengah - Sylvia Vianty Ranita; Sri Wahyuni Mendrofa (Dharma Ekonomi, 2024)
Tourism is one of the key sectors in driving regional economic growth. The potential of tourism attractions contributes to local community income and Regional Original Revenue (PAD) through tourism development. Central Tapanuli Regency has significant tourism potential that can be optimally managed to enhance PAD.This study aims to examine the extent to which the tourism sector contributes to increasing PAD and boosting the local economy in Central Tapanuli Regency. The research employs a quantitative approach using OLS regression analysis based on secondary data collected from the Central Bureau of Statistics of Central Tapanuli Regency from 2014 to 2023.The findings indicate a positive relationship between tourist visits, both domestic and international, and PAD. However, hotel occupancy rates show a negative correlation with PAD. Interestingly, this study highlights that hotel occupancy rates have a negative relationship with PAD. This finding suggests that the government needs to pay attention to factors affecting hotel occupancy rates, such as changing tourism trends and management leakage.The implementation of this research emphasizes the need for policy evaluation and enhanced supervision of hotel occupancy rates.